An Study On Organizational Climate Of The Selected Sugar Mills In Tamil Nadu - CHITRA, R.; RAJAKUMARI, DR.D. (The journal of contemporary issues in business and government, 2021)
The organisational atmosphere is the common experience of workers who work and live in the organisation. It is the sum of people's opinions about an organization's procedures, policies, and activities. It represents the psychological environment of the company, which is made up of individual perspectives framed over time on micro events that affect them and those around them. It is a set of measurable work environment characteristics that have an effect on the participants' job and happiness, either directly or indirectly. Employees' knowledge of organisations and their work is shaped and enhanced by organisational climate variables. With innovative individual motivation to exchange knowledge among group members, a cooperative environment unlocks the right to use among group members and offers more efficiency. In order to boost the country's economic situation, corporate management should strive to create a welcoming organisational atmosphere. The sugar industry plays a complementary role in generating foreign exchange. Apart from text tails, the sugar industry is the largest in the manufacturing sector, employing thousands of technicians and a shortage of trained and unskilled workers. Thousands of people are still involved in the sugar trade and the transportation of sugar cane. As a result, the study focuses primarily on the organisational climate of selected sugar mills in Tamil Nadu.